One-Step Reverse Transcriptase PCR Method for Detection of Borrelia burgdorferi mRNA in Mouse Lyme Arthritis Tissue Samples - Limbach, F. X. (American Society for Microbiology, 1999)
A one-step reverse transcriptase PCR (RT-PCR) method for detection of Borrelia burgdorferi mRNA in infected C3H mice is described. This simple procedure, less prone to nucleic acid cross-contamination than the standard method, was found to be 10-fold more sensitive than a classical two-step RT-PCR assay. By using one-step RT-PCR, flagellin mRNAs were detected in synovial and heart tissues from all seven infected mice tested.